A Breath of Fresh Air / Une boufée d’air frais: Abstracts from the 2012 Canadian Respiratory Conference: April 26 – 28, 2012, Vancouver, British Columbia - Wilcox, Pearce (Pulsus Group Inc, 2012)
The present online supplement highlights the poster abstracts selected for presentation at the 5th Annual Canadian Respiratory Conference (CRC) held in Vancouver, British Columbia, in April 2012. The CRC is a partnership initiative of the Canadian Thoracic Society, Canadian Respiratory Health Professionals, The Lung Association and the Canadian COPD Alliance and has become the premiere national educational and scientific meeting for the respiratory community in Canada. I would like to acknowledge the leadership and expertise of the Scientific Committee, our conference speakers and abstract presenters, all of whom contributed to the delivery of an excellent program. The next Canadian Respiratory Conference will be held in Québec City, Quebec, April 11 to 13, 2012 (www.lung.ca/crc). We look forward to seeing you there!